Eximination of Leisure Spending Habits Broken Down by Weekdays and Weekends - Baba, Erika; Kozma, Tímea; Pálinkás, Réka; Popovicsné Szilágyi, Zita (Acta Carolus Robertus, 2023)
In today’s modern world, recreation plays an increasingly important role, as one of its most important goals is to maintain health and increase our ability to work. The past few years have been defined by the Covid-19 pandemic. As a result, many areas of life have changed, such as health, the economy, education, entertainment and travel. After the introduction of restrictions, we spent more time at home, so activities in our free time also changed. It is important to make good use of the extra time available to us in addition to work.The aim of the study was to observe how busy the participants spend their days and how much time they spend on each activity. The research was conducted using an online questionnaire in which 343 people participated. In terms of gender distribution, women accounted for 72% and men for 28%. The survey covered active and passive actions. The questions covered separate weekdays and weekends, thus providing a comprehensive picture of leisure habits.